PENGARUH ROA DAN NPM TERHADAP RETURN SAHAM - Nida Putri Rahmayanti; Imawati Yousida; Susmita Dian Indiraswari (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
This research aims to examine the effect of return on assets (ROA), net profit margin (NPM) on stock returns listed in food and beverage companies listed on the IDX for the 2018-2021 period. The statistical tool used in this research is Eviews version 12. The research results show that ROA has an effect on stock returns, and NPM has no effect on stock returns.